CHALLENGES FOR INTEGRATION OF REMOTELY PILOTED AIRCRAFT SYSTEMS INTO THE EUROPEAN SKY - Tadeusz ZIELIŃSKI; Wiesław MARUD (Scientific Journal of Silesian University of Technology. Series Transport)
Remotely Piloted Aircraft Systems (RPAS) are widely used in the civil sphere. They offer capabilities predisposed them to be employed by state services in ensuring security and public order, as well as in commercial activities. It should be assumed that the number of RPAS users will grow in geometric progression. It also applies to the European Union, where the market of RPAS is considered to be one of the most prospective in the development of small and medium-sized enterprises. This situation generates specific problems that should be solved in order to develop the RPAS’ market without limitations as a part of the European aviation system. The final state should be full integration of RPAS into the European aviation system, to conduct flight operations in non-segregated airspace without additional administrative constraints. Some efforts have been made to achieve this ambitious goal in the European Union. The paper summarises the current status of the legal framework and projects connected with the integration of RPAS into the European airspace. It is mainly based on qualitative analysis of source materials. The purpose of the paper is to identify key problem areas, the solution of which will contribute to the integration of RPAS into the European civil aviation system. An analysis of normative documents functioning in the European Union (EU) relating to RPAS has been carried out. In particular, the European Commission (EC) documents and regulations related to RPAS proposed by the European Aviation Safety Agency (EASA) have been taken into account. Three crucial areas have been identified as challenges for the integration of RPAS into the European civil aviation system. Firstly, general concepts of integration of Remotely Piloted Aircraft into the European airspace including the development of the U-space concept. Secondly, the field of legal regulations, without which the functioning of RPAS as a part of the European aviation system is impossible. In this context, it is justified to continue the implementation of the Roadmap for the integration of civil Remotely-Piloted Aircraft Systems into the European Aviation System proposed by the EC in 2013. Also relevant are the EASA proposals for categorising RPAS and conducting flight operations based on the risk approach which is a new solution. The discussion may be triggered due to by-pass of all regulatory competencies to EASA, without taking into account the specificity of the national systems. Thirdly, the societal field. Full integration of RPAS into the European civil aviation system requires social acceptance for air operations involving RPAS. Despite the undeniable social benefits of RPAS utilisation, in particular in ensuring security and public order, it will be necessary to address issues related to the perception of RPAS by the public, including privacy and data protection, law enforcement associated with the application of RPAS, third-party liability and insurance requirements of RPAS.